THE EFFECT OF NEUROLOGICAL MUSIC THERAPY ON ORAL INTAKE IN PRETERM CHILDREN - Červenková, Barbora (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Preterm birth is associated with increased risk of neurological, cognitive, motor or sensory impairment and behavioral problems. Music therapy appears to promote neurobehavioral outcomes and can improve brain structure functions.The aim of the study presented in the article is to analyse a potential of a special music therapy technique to shorten time to achieve full oral intake in children born extremely preterm, to (<28 weeks) with bronchopulmonary dysplasia (BPD). We used the mother's singing during breastfeeding, with the slow tempo (60 beats per minute) and a recurring pattern of stressed (strong) and unstressed (weak) syllables (each second was highlighted) to help preterm babies to organize coordination of sucking swallowing and breathing. This therapeutic approach is based on the theory and methods of neurological music therapy called Patterned Sensory Enhancement (PSE). A total of 40 children were included in this Oxford pretest - posttest study design. The experimental group used the PSE intervention technique (n = 20) was compared with the control group of children (n = 20) without the specific therapy.